2009
DOI: 10.1242/jcs.037200
|View full text |Cite
|
Sign up to set email alerts
|

The scavenger receptor CD36 plays a role in cytokine-induced macrophage fusion

Abstract: Multinucleated giant cells, characteristic of granulomatous infections, originate from the fusion of macrophages. Using an antibody screening strategy we found that the scavenger receptor CD36 participates in macrophage fusion induced by the cytokines IL-4 and GM-CSF. Our results demonstrate that exposure of phosphatidylserine on the cell surface and lipid recognition by CD36 are required for cytokine-induced fusion of macrophages. We also show that CD36 acts in a heterotypic manner during giant-cell formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 34 publications
4
112
0
3
Order By: Relevance
“…(DC-STAMP) and E-cadherin. 47,[67][68][69][70] It was proposed that these molecules may act as co-receptors for membrane attachment, as illustrated by the example of CD36, 69 or as chemokine receptors (e.g., DC-STAMP), 71 or they may trigger other yet unknown molecules that initiate the membrane fusion events.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…(DC-STAMP) and E-cadherin. 47,[67][68][69][70] It was proposed that these molecules may act as co-receptors for membrane attachment, as illustrated by the example of CD36, 69 or as chemokine receptors (e.g., DC-STAMP), 71 or they may trigger other yet unknown molecules that initiate the membrane fusion events.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…CD36 acts as a facilitator of fatty acid uptake and is a receptor for a wide range of ligands including collagen, thrombospondin, anionic phospholipids, oxidized low density lipoprotein and erythrocytes parasitized with P. falciparum [6][7][8], and participate in macrophage fusion induced by IL-4 cytokines [9].…”
Section: Introductionmentioning
confidence: 99%
“…To determine where EFF-1 is required, we expressed a GFP-tagged version of this protein Furthermore, double mutants between eff-1 and psr-1 were no more defective than eff-1 mutants (Figure 2.2b), indicating that psr-1 and eff-1 are in the same genetic pathway. PSR-1 contains two highly conserved functional domains, an extracellular lysine-rich PS binding domain 21 , and an intracellular JmjC domain with multiple enzymatic activities [22][23][24] . We expressed different versions of full-length psr-1 cDNA selectively in the mechanosensory neurons of psr-1 mutant animals.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…We used the Squassh imaging tool (ImageJ) 24 to automatically select and measure these puncta. We found that increasing RAB-5 activity with RAB-5(CA) caused accumulation of EFF-1 within enlarged intracellular puncta (Figure 3.4a).…”
Section: Rab-5 Controls Eff-1 Localization To Intracellular Compartmentsmentioning
confidence: 99%
See 1 more Smart Citation